Global, regional, and national burden of cardiovascular disease attributable to high body mass index from 1990 to 2021 and projection to 2045 - Li, Hui; Liang, Lifang; Song, Zhenyu; Li, Yongfeng (Frontiers in Endocrinology, 2025)
BackgroundHigh body mass index (HBMI) is strongly associated with cardiovascular disease (CVD), but the global burden of CVD attributable to HBMI remains poorly defined. This study aims to elucidate the current burden and temporal trends of CVD attributable to HBMI.MethodsWe used data from the Global Burden of Disease Study (GBD) 2021 to estimate CVD deaths and disability-adjusted life years (DALYs) attributable to HBMI. Our analysis examines trends in deaths and DALYs by age, gender, and Socio-demographic Index (SDI) across global, regional, and national levels from 1990 to 2021. We used health inequality and decomposition analyses to quantify the influencing factors of disease burden and a Bayesian age-period-cohort (BAPC) model to predict the potential trend of HBMI on CVD burden.ResultsIn 2021, HBMI-related CVD resulted in approximately 1.9 million deaths and 45.43 million DALYs among urban and rural populations, with an age-standardized mortality rate (ASMR) of 22.77 (95% UI, 12.87-34.24) and an age-standardized disability rate (ASDR) of 529.00 (95% UI, 277.28-808.64) per 100,000 people. Over the study period, the overall CVD burden attributable to HBMI decreased significantly, while the burden of atrial fibrillation and flutter increased. The disease burden was closely tied to socioeconomic development and was unevenly distributed, with middle SDI regions experiencing a heavier burden. The highest burden was observed in individuals aged 84 and older, with a significant increase in the 20–44 age group. Decomposition analysis revealed that the increase in DALYs was driven by population growth. Projections from the BAPC model suggest that by 2045, global DALYs of CVD attributable to HBMI may continue to increase.ConclusionsThis study provides a comprehensive epidemiological assessment of the CVD burden attributable to HBMI across various regions and populations, offering valuable insights for guiding policy and research efforts.